Employee Gender Characteristics Among Retail Sectors - Chang, Joshua; Travaglione, Tony (Society for Global Business & Economic Development (SGBED), 2011)
Employee gender characteristics vary among different retail sectors. For example, male dominated retail sectors such as hardware employ more male staff, while female dominated retail sectors such as cosmetics employ more female staff. The purpose of this paper is to explain such gender differences in retail employment. The data used for this study is a subset of the ‘Australia at Work’ survey, which is a longitudinal survey tracking the experiences of the Australian labour force via telephone interviews. In answering the research questions, a subset of telephone interview data from the ‘Australia at Work’ survey consisting of 702 respondents employed in the retail industry will be analysed. The results indicate that retail employment in Australia is dominated by females, and that certain retail sectors were found to have different employee gender characteristics. Managerial positions in retail were found to have only a slightly larger proportion of males, implying that there is little gender discrimination in retail managerial positions in Australia as compared to findings from the United Kingdom and the United States. Customers are likely to have preferences as to who they are being served by when shopping for specific products, affecting their purchase decisions and consequently the business performance of stores. Hence, managers can use such information in employment decision making to create a competitive advantage and increase profitability.